School heads' responses to instructional, administrative, and supervisory challenges: inputs for a training guide on adversity response - Rosales, Ma. Celina N. (San Miguel, Iriga City: University of Saint Anthony, 2017)
School heads' responses to instructional, administrative, and supervisory challenges: inputs for a training guide on adversity response.
Includes bibliographical references.
English
Keywords: Training guide